Design and performance of a new setup for spatially resolved transmission X‐ray photoelectron spectroscopy at the Swiss Light Source. (2nd April 2019) - Roy, Kanak; Raabe, Joerg; Schifferle, Pascal; Finizio, Simone; Kleibert, Armin; van Bokhoven, Jeroen A.; Artiglia, Luca
Abstract : The design and development of a photoelectron spectromicroscope working in transmission mode are presented. Abstract : The successful design, installation and operation of a high spatial resolution X‐ray photoelectron spectrometer at the Swiss Light Source is presented. In this instrument, a Fresnel zone plate is used to focus an X‐ray beam onto the sample and an electron analyzer positioned at 45° with respect to the incoming beam direction is used to collect photoelectrons from the backside of the sample. By raster scanning the sample, transmitted current, X‐ray absorption and X‐ray photoemission maps can be simultaneously acquired. This work demonstrates that chemical information can be extracted with micrometre resolution; the results suggest that a spatial resolution better than 100 nm can be achieved with this approach in future. This kind of photoelectron spectromicroscope will allow in situ measurements with high spatial resolution also under ambient pressure conditions (in the millibar range). Element‐specific X‐ray photoemission maps can be obtained before and while exposing the sample to gas/gas mixtures to show morphological and chemical changes of the surface.